2022
DOI: 10.3389/fmolb.2022.928399
|View full text |Cite
|
Sign up to set email alerts
|

Opposing Roles of Wild-type and Mutant p53 in the Process of Epithelial to Mesenchymal Transition

Abstract: The central role of an aberrantly activated EMT program in defining the critical features of aggressive carcinomas is well documented and includes cell plasticity, metastatic dissemination, drug resistance, and cancer stem cell-like phenotypes. The p53 tumor suppressor is critical for leashing off all the features mentioned above. On the molecular level, the suppression of these effects is exerted by p53 via regulation of its target genes, whose products are involved in cell cycle, apoptosis, autophagy, DNA re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 94 publications
1
15
0
Order By: Relevance
“…Interestingly, we found that the K tumor organoids are almost depleted of the Hmga2-high Group 4, raising the possibility that Kras G12D mutation alone cannot drive AT2 cells to acquire the Hmga2-high Group 4 state, at least at the 7 day timepoint. This is consistent with previous findings that P53 loss can promote EMT-program activation 37,38 . These results may suggest that tumors with different oncogenic genotypes may differ in cell states composition, providing further proof of concept for using the organoids system to dissect phenotypic variations in tumorigenesis.…”
Section: Spc-high Cells and Hmga2-high Cells Represent Distinct Path ...supporting
confidence: 94%
“…Interestingly, we found that the K tumor organoids are almost depleted of the Hmga2-high Group 4, raising the possibility that Kras G12D mutation alone cannot drive AT2 cells to acquire the Hmga2-high Group 4 state, at least at the 7 day timepoint. This is consistent with previous findings that P53 loss can promote EMT-program activation 37,38 . These results may suggest that tumors with different oncogenic genotypes may differ in cell states composition, providing further proof of concept for using the organoids system to dissect phenotypic variations in tumorigenesis.…”
Section: Spc-high Cells and Hmga2-high Cells Represent Distinct Path ...supporting
confidence: 94%
“…69 Since EMT-TFs can likewise inhibit p53 and other tumor-suppressive programs, it appears that a sophisticated mutual inhibition of EMT and p53 is governing EMT commitment and tumor suppression versus malignancy. 70,71 Intriguingly, in our study, there was no apparent dependence of the ZEB1 hi phenotype on p53 status across the various cell lines we used, i.e., MCF10A (p53 wild-type [WT]), HCT116 (p53WT), A549 (p53WT), J82 (p53 mutant [mut]), Panc1 (p53 mut), and MDA-MB-231 (p53 mut). We thus conclude that p53 status seems not to dramatically affect the role of ZEB1 promoting S-phase entry triggering sub-lethal DNA replication stress.…”
Section: Discussionmentioning
confidence: 57%
“…Among all these genes only MMP9 resulted in signi cant survival increase depending on p53. Given that p53 may regulate not only gene expression but also protein stability of EMT transcription factors like SNAIL and TWIST1 in HCC and in diverse tumor cells 47,53,54 , and considering that protein escindition of E-cadherin by metalloproteinases like MMP9 is also a way of EMT regulation in different cancers 55,56,57 , the complete picture is missing in transcriptomic analyses. Proteomic analyses from patients organized in databases are still scarce, but further studies would be necessary in HCC to nd actual EMT determinants of the disease progression.…”
Section: Discussionmentioning
confidence: 99%